Peritendinous injection of platelet-rich plasma to treat tendinopathy: A retrospective review - Mehmet Can Unlu; Aybars Kivrak; Mahmut Enes Kayaalp; Olgar Birsel; Isık Akgun (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to determine factors associated with the likelihood of a better clinical outcome after the peritendinous injection of PRP for the treatment of chronic tendinopathy and identify whether PRP represents an effective treatment option for chronic tendinopathies. Methods: The study included 214 patients (86 males and 128 females; mean age: 39.3 (18–75) years) who received PRP injections for tendinopathy refractory to conventional treatments. The mean duration of symptoms at the moment of the PRP treatment was 8.3 months. Primary outcome measurement was perceived improvement in symptoms for each anatomic compartment for upper and lower limbs at 6 months after treatment. Also, a visual analog scale (VAS) score (pain intensity on a 0–10 scale) was used for pain scoring questionnaire before treatment, 6 weeks and 6 months following the PRP injection(s). To identify factors associated with the likelihood of a better clinical outcome, patients were categorized on the basis of their perceived improvement in symptoms 6 months after the PRP injection(s)—that is, as lower (less than 50% global improvement) or higher (more than 50% global improvement). Results: A visual analogue scale score and perceived improvement in symptoms were significantly lower after peritendinous injection in 6-week and 6-month follow-ups compared with the baseline (P < 0.001) except for peroneal and Achilles tendons. Overall, 83% of patients indicated moderate to complete improvement in symptoms. The most common injection sites were the lateral epicondyle, Achilles, and patellar tendons. Furthermore, 30% of patients received only 1 injection, 30% received 2 injections, and 40% received 3 or more injections. A total of 85% of patients were satisfied (more than 50% global improvement) with the procedure. In addition, upper limb tendons, increase in the age, and female gender were associated with a higher likelihood of perceived improvement in symptoms. Conclusions: In the present retrospective study assessing PRP injections in the treatment of chronic tendinopathy, a moderate improvement (>50%) in pain symptoms was observed in most of the patients. Our research found that results were most promising with patellar and lateral epicondylar tendinopathy in the short to medium term. Female patients, patients with upper extremity tendinopathy and older patients appeared to benefit more from PRP injection. Level of evidence: Level IV, Therapeutic study. Keywords: Platelet-rich plasma, Tendinopathy, Injection, Achilles tendon, Patellar tendon, Lateral epicondylitis